Determinants of Decision to Visit the Bukit Gundaling Berastagi Tourist Attraction with Satisfaction as an Intervening Factor - Shin Tia, Resa; Ikhsan Harahap, Muhammad (Jurnal Ad'ministrare: Jurnal Pemikirian Ilmiah dan Pendidikan Administrasi Perkantoran, 2024)
This research is motivated by the decline in visitor interest in traveling to the Gundaling Hill tourist attraction and the many complaints from visitors after visiting Gundaling Hill Berastagi in the form of criticism and suggestions. The criticism and suggestions indicate dissatisfaction among visitors after visiting Gundaling Hill Berastagi which may be caused by reduced visitor satisfaction with the management. This study aims to analyze the influence of visitor satisfaction on visiting decisions. The data analysis used in this study is descriptive and quantitative. The sample in this study were people who had visited Gundaling Hill Berastagi, totaling 96 people. Data collection was carried out using a questionnaire tested for validity and reliability. Data were analyzed using path analysis with a multiple linear regression model. The results of statistical tests show that the product variable has a positive effect on the intention to revisit (hypothesis 1 is accepted), the price variable has a positive effect on visitor satisfaction (hypothesis 2 is accepted), the place variable has a positive effect on visitor satisfaction (hypothesis 3 is accepted), the promotion variable has a positive effect on visitor satisfaction (hypothesis 4 is accepted), the regulation variable has a positive effect on visitor satisfaction (hypothesis 5 is accepted), the visitor satisfaction variable has a positive effect on the decision to visit (hypothesis 6 is accepted), the 4p+regulation variable does not have a positive effect on the decision to visit through visitor satisfaction.  . This study identifies factors such as product, price, place, promotion, and regulation that influence satisfaction and visitation decisions, but focuses on how visitor satisfaction mediates these relationships. This novelty provides tourism managers with insights into the importance of focusing on visitor satisfaction as a key element in increasing repeat visitation intentions, especially in local contexts that have rarely been analyzed before.